Reduced expression of the DNA glycosylase gene MUTYH is associated with an increased number of somatic mutations via a reduction in the DNA repair capacity in prostate adenocarcinoma. Issue 2 (10th June 2016) - Shinmura, Kazuya; Kato, Hisami; Kawanishi, Yuichi; Yoshimura, Kimio; Igarashi, Hisaki; Goto, Masanori; Tao, Hong; Inoue, Yusuke; Sugiyama, Takayuki; Furuse, Hiroshi; Ozono, Seiichiro; Sugimura, Haruhiko
Abstract : 8‐Hydroxyguanine (8OHG), a major oxidative DNA lesion, is known to accumulate in prostate cancer; however, the status of one of its repair enzymes, MUTYH, in prostate cancer remains to be elucidated. In this study, we showed that the expression levels of MUTYH mRNA and protein were significantly lower in prostate cancer than in non‐cancerous prostatic tissue by examining two independent, publicly available databases and by performing an immunohistochemical analysis of prostate cancer specimens obtained at our hospital, respectively. About two‐thirds of the prostate cancers exhibited a reduced MUTYH expression. When the effect of reduced MUTYH expression in prostate adenocarcinoma on the somatic mutation load was examined using data from the Cancer Genome Atlas (TCGA) database, the numbers of total somatic mutations and somatic G:C to T:A mutations were significantly higher in the reduced MUTYH expression group than in the other group ( P < 0.0001 and P = 0.0013, respectively). To determine the reason why reduced MUTYH expression leads to somatic mutation loads in prostate adenocarcinoma, we compared the DNA repair capacities between PC‐3 prostatic cell line derived clones with different MUTYH expression levels. Both the capacities to cleave DNA containing adenine:8OHG mispairs and to suppress mutations caused by 8OHG were significantly lower in prostatic cell lines with lower MUTYH expression than in prostatic cell lines with higher MUTYH expression. These results suggested that reduced MUTYH expression is associated with somatic mutation loads via a reduction in DNA repair capacity in prostate adenocarcinoma. © 2016 Wiley Periodicals, Inc.